Effects of consumer ethnocentrism of Malaysian working women on their purchasing behaviour of halal cosmetic products - Kaur, Kamaljeet (2015)
The wave of globalization has impacted various industries including the cosmetics industry in Malaysia. The availability of various international brands and home grown brand has given the consumers the luxury to choose a wide variety of cosmetics which are available in the market place. Thus, it is crucial for the Malaysian made halal cosmetic industry to understand factors that influences the purchasing behaviour of the consumers in particular the Malaysian working women which is a fast growing market segment. The country of origin effect has a positive or negative influence the consumers’ selection process and behaviour and is based one’s ethnocentric tendencies. Highly ethnocentric consumers feel they should buy products manufactured in their home country only. The aim of this study is to determine the moderating effect of consumer ethnocentrism of the Malaysian working women on the purchasing behaviour of the Malaysian made Halal cosmetic products. The underlying theory and concepts used in the research framework is from the Theory of Planned Behaviour, Cultural Openness, Global Openness and the Consumer Ethnocentrism concept. A survey technique was conducted among 425 Malaysian working women using mall-intercept method. The SmartPLS software application for Partial Least Squares Structural Equation Modelling (PLS-SEM) is used to analyse the data. The results showed the model’s explanatory variance is strong with perceived behavioural control having the most important predictive variable. The moderating effect of the consumer ethnocentrism increased the predictability of the model with an effect of medium to large moderator effect.of Iranians from 1980 to 2010. In a general overview of HDI outputs, it appears that Iran has benefited with a relatively acceptable rate of improvement in HDI and its indices. So, the results this study, poverty and inequality were shown to have generally stagnated at existing levels without any indication of significant improvement and have not significantly decreased in Iran. Thus, our findings demonstrate that social development in Iran is closely related to economic development, while economic improvement depends on the progress of globalization or integration in international relations. By having created a layout for the development contexts in Iran and pointing out the importance of economic competition in the present and future, society can be lead to social and economic development. Consequently, a decrease in poverty and inequality levels will be manifested. Therefore, the issues relate to development and modernization that go beyond national boundaries and that lead to globalization and integration within a global society, with emphasis on socioeconomic developments, decline of poverty and inequality at all levels in all countries. However, after the introduction of the moderating effect, Global Openness became the most important predictor. The results of the overall study showed before the moderating effect of consumer ethnocentrism, the most important variable was perceived behavioural control. But after the moderating effect was introduced, Global Openness became an important predictor. This could be due to the trust in the Malaysian made Halal cosmetic products which are certified by JAKIM by the respondents. Although the Malaysian working women are in par in the wave of globalization and technology advancement, but when it comes to purchases with regards to religious obligation the products which are made in Malaysia and endorsed Halal becomes an important factor in their purchasing behaviour.